Predicate reference and navigation in ORM - Halpin, Terry (Springer Link, 2009)
A conceptual schema of an information system specifies the fact structures of interest as well as related business rules that are either constraints or derivation rules. The sole data structure used in fact-oriented modeling approaches is the fact type, which may be understood as a set of typed predicates. In spite of the central role played by predicates in fact-orientation, several issues need to be resolved before their full potential can be fully realized. This paper identifies a number of these issues relating to predicate reference and navigation, and proposes some solutions. Specific issues addressed include predicate disambiguation and formalization, role navigation, and automated verbalization of predicate paths. While the discussion focuses largely on Object-Role Modeling (ORM), many of the issues discussed are also relevant to other fact-oriented approaches, such as Cognition enhanced Natural Information Analysis Method (CogNIAM) and the Semantics of Business Vocabulary and Business Rules approach (SBVR), as well as attribute-based approaches like Entity Relationship modeling and the Unified Modeling Language.